A Critique on the Book “The Mixed Method Research” - Mustafa Hamadani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
“The Mixed Method Research” written by Dr. Ali Delavar and Dr. Shirin Koshki has been used as a textbook for human and social sciences in the new field of mixed methods. This book contains some drawbacks which are investigated in the current research. This paper having descriptive and analytical method presents several considerations on formal and contextual criticisms as well as structural criticisms. The researcher criticizes this book for such mistakes as (1) wrong book title, (2) weakness in concept extraction of mixed methods, (3) unpleasant book structure and  inexpressive section headings, (4) long paragraph, (5) spelling, grammar, and editing mistakes, (6) numerous quotations from other sources without reference, (7)  some irrational section headings that are not consistent with the contents, (8) use of ambiguous terms, (9) incorrect graph drawing and numerous problems in their graphic indications, (10) weakness in explaining and proving paradigmatic foundation of mixed methods, and, lastly, (11) introducing the work as authored book while it is translated-authored work.